Pulmonary mucormycosis disseminating locally to cause spinal mucormycosis: An autopsy study - Prasad, Shashi Shekhar; Misra, Pratibha; Sen, Debraj; Kumar, Jatinder; Premsingh, Patwal Rajeev; Sengupta, Prasanta (Annals of Pathology and Laboratory Medicine, 2025)
We present a case, a thirty-six years old male, known case of disseminated pulmonary tuberculosis post anti-tubercular therapy, diabetes mellitus type 3C, chronic pancreatitis and alcohol dependence syndrome. He presented with cough and shortness of breath. Chest X-ray and Non-contrast Computed Tomography showed features of pneumonia involving right upper lobe. Laboratory investigations revealed features of diabetes ketoacidosis. Later, High- Resolution Computed Tomography of thorax revealed consolidation with cavitation in the right upper lobe and multiple nodules with a rim of ground-glass haze (halo sign). During the course of management, he developed rapidly progressive motor deficit of lower limb followed by sensory deficit and loss of deep tendon reflexes. Magnetic resonance imaging of thorax and cervico-dorsal spine showed consolidation and cavitation in the right lung apex with contiguous ipsilateral soft tissue edema of the chest wall, paravertebral soft tissues and marrow edema along the right side of the vertebrae. The spinal cord from the level of C5 to D2 vertebrae was also swollen and edematous. He followed a downhill course and succumbed the illnesses. Postmortem examination revealed cavitatory lesion with invasive pulmonary mucormycosis involving apex of right lung and locally spreading to ipsilateral thoracic wall, paravertebral soft tissue, intervertebral disc, vertebral bone marrow and spinal cord corresponding to D1-D2 thoracic vertebra leading to spinal mucormycosis. Spinal mucormycosis is extremely uncommon and present case being the twelfth case. To the best of our knowledge only one case of locally spreading pulmonary mucormycosis leading to spinal mucormycosis has been reported till date.